Association of maternal serum triglycerides at term and macrosomia in gestational diabetes mellitus - S., Dhivya Bharathi; Akoijam, Usharani; Pratima Devi, Khumanthem; Ajitkumar Singh, Yanglem; Kongkham, Tarunibala Devi; Gowdhami, S.; Tauro, Sheral Raina; Paul, Papiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of the study was to determine association of maternal serum triglycerides (TG) at term and macrosomia in gestational diabetes mellitus (GDM). Methods: A cross sectional study was carried out in the department of obstetrics and gynaecology, RIMS, Manipur. The study was conducted for 2 years duration from September 2019 to August 2021 and 85 singleton term pregnant women with GDM were included. All the patients were subjected to check fasting serum TG, FBS, PPBS. Descriptive statistics like mean, standard deviation and Inferential statistics like Chi-square test was used for comparing study variables between large for gestational age (LGA) and non LGA group. T-test was used to compare the mean values of age, pre-pregnancy BMI, pregnancy weight gain, OGTT, FBS, PPBS, fasting serum TG between LGA and non LGA group. Results: The observed mean TG values in LGA and non LGA group in our study was 262.35±26.08 and 158.18±13.24 mg/dL respectively. The serum TG values in the LGA group mothers was significantly higher when compared to the non LGA group. The mean weight gain in pregnancy 15.17±1.82 and 9.60±1.47 in LGA and non LGA respectively. The mean BMI comparison among LGA and non LGA are 27.7±1.74 and 22.94±1.6 respectively. Conclusions: It is observed that maternal fasting serum TG may be a strong predictor of foetal size irrespective of the glycemic status. Our study clearly pointed out the usefulness of measuring serum TG in GDM pregnancy. In addition to maternal hypertriglyceridemia, pre-pregnancy BMI, excessive weight gain in pregnancy significantly associated with foetal macrosomia in GDM mothers.